PEMBELIAN PRODUK SMARTPHONE OPPO PADA STORE OMEGA CELL SIMPUR CENTER DI BANDAR LAMPUNG - Sari, Yuli Mayang (Universitas Mitra Indonesia, 2023)
This research aims to determine the influence of the marketing mix on purchasing decisions for Oppo smartphone products at the Omega Cell Simpur Center Shop in Bandar Lampung. The sample in this research was the Omega Cell Simpur Center Shop in Bandar Lampung, totaling 72 respondents. Primary data in this research was obtained through questionnaires distributed to respondents and secondary data in this research was a list of products and sales as well as a price list for Oppo smartphones at the Omega Cell Simpur Center Shop in Bandar Lampung. The analysis techniques used are data quality testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. Based on the results of data analysis, it can be concluded that the marketing mix consisting of product, price, location and promotion has a positive and significant partial and simultaneous effect on purchasing decisions for Oppo smartphone products at the Omega Cell Simpur Center Shop in Bandar Lampung